Developing Content for 4-Side Hologram Media: E-Book and Hologram Video on Sound Material for Junior High School Students - Andini, Putri Ayu; Setiawan, Agung Mulyo (Universitas Negeri Malang, 2022)
From the result of literature review, hologram as learning media is able to attract student interest and learning, and it is suitable to use in various disciplines and levels of education. In other hand, the observational result in the field, teachers rarely used an innovative media and student learning outcomes are low in sound material. Therefore, the authors are interested in developing hologram media content forms as e-books and hologram videos on sound material. This research is using R&D method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluate). Based on our result, it can be concluded that the development of e-books and hologram videos on sound material are valid with a percentage 88.5% and are suitable to use in the classroom with a percentage 89.4%. Likewise, from the result of the reliability test for pre-test and post-test questions has a value of 0.882, so that these questions are reliable. After these products are used in the classroom, the effectivity test with N-gain experienced value in a moderate category. Thus, it can be concluded that the development of hologram media content for sound material, such as e-book and hologram videos, are effective to use in junior high school.